2009
DOI: 10.1017/s0022112008005107
|View full text |Cite
|
Sign up to set email alerts
|

Dye visualization near a three-dimensional stagnation point: application to the vortex breakdown bubble

Abstract: An analytical model, based on the Fokker–Planck equation, is constructed of the dye visualization expected near a three-dimensional stagnation point in a swirling fluid flow. The model is found to predict dye traces that oscillate in density and position in the meridional plane in which swirling flows are typically visualized. Predictions based on the model are made for the steady vortex breakdown bubble in a torsionally driven cylinder and compared with computational fluid dynamics predictions and experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Thompson & Hourigan (2003) showed that small errors in the rotating end-cover produced surprisingly strong asymmetries in the flow, a finding supported with fully three-dimensional numerical simulations in Brons et al (2007). Further work showed that the accuracy of injection of visualization dye in experiments was itself sufficient to give rise to asymmetric flow (Brons, Thompson & Hourigan 2009). …”
Section: Resultsmentioning
confidence: 71%
“…Thompson & Hourigan (2003) showed that small errors in the rotating end-cover produced surprisingly strong asymmetries in the flow, a finding supported with fully three-dimensional numerical simulations in Brons et al (2007). Further work showed that the accuracy of injection of visualization dye in experiments was itself sufficient to give rise to asymmetric flow (Brons, Thompson & Hourigan 2009). …”
Section: Resultsmentioning
confidence: 71%
“…These asymmetries are due to flow structural instability and experimental imperfections in the location of the injection hole and in the alignment of the rotating top disk. 38,40,41 At late stages, the dye slowly fills the two bubbles and becomes thicker due to the molecular diffusion ͓see Fig. 4͑c͔͒.…”
Section: Vortex Breakdown Visualization With Neutrally Buoyant Dmentioning
confidence: 99%
“…Experiments and calculations have indicated that very slight asymmetries in the TDC geometry, i.e., very slight structural asymmetries, can lead to clearly asymmetric flows. 32,33 In addition, slight visualisation technique asymmetries, such as slight misalignments in dye injection 34 and dye diffusion 35 can lead to strongly asymmetric visualisations even for strictly symmetric flows. The onset of precession of the breakdown bubbles in the TDC has, however, been observed for high Reynolds numbers 36,37 and at cylinder aspect ratios above 3.3, asymmetry has also been observed.…”
Section: Introductionmentioning
confidence: 99%